Affective and cognitive influence of control of navigation on cause sponsorship and non‐profit organizations. Issue 4 (6th July 2015) - Wang, Ye
<x xml:space="preserve">Abstract</x> The purpose of this research is to examine how control of navigation influences cognitive and affective sponsorship responses and attitude towards the non‐profit organization in the context of corporate websites. By conducting experiments on fictitious brands and existing non‐profit organizations, this study found that control of navigation did not influence sponsorship cognition. Attitude towards the website fully mediated the influence of control of navigation on attitude towards the sponsor's brand and attitude towards the non‐profit organization. Additionally, high control of navigation in combination with high perceived fit was associated with the most positive brand attitude. These findings suggest that control of navigation defined as an external control factor is primarily an affective heuristic; in addition, the heuristic processing influences not only the sponsor's brand but also the sponsored non‐profit organization. Practically, this study suggests that the navigation of corporate websites has to be user‐friendly in order to benefit the brand and ensure neutrality of consumers' judgement of the sponsored non‐profit organization. Copyright © 2015 John Wiley & Sons, Ltd.